PENGEMBANGAN MEDIA MINIATUR UNTUK REGULASI DIRI ANAK USIA 5-6 TAHUN DI TK FKIP UNRI - Sari, Hesti Kumala; N, Zulkifli; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: Miniature media for self-regulation for children aged 5-6 years wasdeveloped as a response to children who cannot say the number of hours, do not yetknow the form of waking up and coming home from school. The type of research used isdevelopment research (Research and Development). The steps taken are potential andproblems, data/information collection, design, design validation, design revision, andproduct testing. Data collection techniques using observation, questionnaires anddocumentation. The instrument used is a questionnaire for validation of MiniatureMedia from media experts, material experts and educational experts. The data analysistechnique used is quantitative descriptive analysis technique. In the research, mediaexpert validation was obtained (88.60%), material expert validation (93.75%), andeducator validation (85.83%). The results of the limited trial assessment were (88.33%)with the category